As A Result Of The Laws Of Buying And Sale Of Used Land Of Eigendom State Which Is Conducted Under Hands - Al Ayubi, Aji Ilham; Karjoko, Lego; Waluyo, Waluyo (International Journal of Educational Research & Social Sciences, 2024)
The purpose of this research is to analyze the legal consequences of a land sale and purchase agreement under a former eigendom right (customary law) based on customary law and Government Regulation Number 24 of 1997 concerning land registration. The study also aims to construct the procedure for land registration applications on the former eigendom right based on current applicable regulations. This research adopts a normative legal research approach with legislative and conceptual approaches. The results of the research indicate that a land sale and purchase agreement under a former eigendom right cannot be registered with the land office as the institution issuing land certificates, even though the agreement is considered legally valid under customary law because it adheres to the principles of real, cash, and clear. The land office accepts the application for registration of land under the former eigendom right based on the regulations, namely the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Regulation Number 18 of 2021 concerning Procedures for Determining Management Rights and Rights to Land, Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Regulation Number 3 of 2020 concerning Procedures for Determining and Registering Rights to Land Formerly Owned by Individual Citizens of the Netherlands or Legal Entities Owned by the Netherlands, Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Regulation Number 16 of 2022 concerning Delegation of Authority for Determination of Land Rights and Land Registration Activities, and Minister of Finance Regulation Number 31/PMK.06/2015 of 2015 concerning Settlement of Former Foreign/Chinese-Owned Assets.